Análisis de reducción de costos de producción en la planta CEDAL. - Pichogagón Pulamarín, Cristian David (2019)
This work is carried out with the objective of obtaining, an analysis to reduce the costs of production, that has the Ecuadorian Corporation of Aluminum CEDAL S. A in its melting area, due to an increase that has been produced by the concept of the Labor, and of the raw material used in the melting process. For that, it was taken as objectives to know the processes involved that are carried out in the melting area of the CEDAL Company, as well as costs of them to then raise a strategy enabling to reduce the items mentioned above in these processes. In order to comply with the proposed objectives, the project will be enclosed in the diagnosis and analysis of data that will be obtained by means of the observation and the collection of primary data provided by the company, as well as those obtained by own elaboration. After that, data was collected by bibliographic sources according to similar projects will be used. The data found are going to be previously analyzed and tabulated, allowing to making use of graphics and visual indicators of the problems detected in that area. The calculations of the strategy for the reduction of costs by Labor concepts will be linked with the rules in force in the Labor Code and previously compared so that the company takes the appropriate measures for the implementation or not, of this strategy raised. The importance of conducting this analysis lies in the social aspects because comes into play the human factor in this case the labor present in the workers of the smelting area of the CEDAL Company. And in the economic part looks for a better management of these items that are essential to obtain a cash flow, providing an adequate utility to both the company and the workers.